Pulmonary Delivery of Metoprolol Reduces Ventricular Rate During Atrial Fibrillation and Accelerates Conversion to Sinus Rhythm. Issue 2 (February 2020) - Marum, Alexandre A.; Araujo Silva, Bruna; Bortolotto, Alexandre L.; Pedreira, Giovanna C.; Tessarolo Silva, Fernanda; Medeiros, Sofia A.; Nearing, Bruce D.; Belardinelli, Luiz; Verrier, Richard L.
Abstract : Background: Safe, effective pulmonary delivery of cardioactive agents in humans is under development. Objectives: We examined whether intratracheal delivery of metoprolol can reduce ventricular rate during atrial fibrillation (AF) and accelerate conversion to sinus rhythm. Methods: In 7 closed-chest, anesthetized Yorkshire pigs, AF was induced by intrapericardial infusion of acetylcholine (1 mL of 102.5-mM solution) followed by atrial burst pacing and was allowed to continue for 2 minutes before intratracheal instillation of sterile water or metoprolol (0.2-mg/kg bolus) using a catheter positioned at the bifurcation of the main bronchi. High-resolution electrograms were obtained from catheters fluoroscopically positioned in the right atrium and left ventricle. Results: Rapid intratracheal instillation of metoprolol caused a 32-beat/min reduction in ventricular rate during AF (from 272 ± 13.7 to 240 ± 12.6 beats/min, P = 0.008) and a 2.3-minute reduction in AF duration (from 10.3 ± 2.0 to 8.0 ± 1.4 minutes, P = 0.018) compared with sterile water control. Conversion of AF to sinus rhythm was associated with rapid restoration (5–6 minutes) of heart rate and arterial blood pressure toward control values. Intratracheal metoprolol reduced AF dominant frequency by 31% (from 8.7 ± 0.9 to 6.0 ± 1.1 Hz, P = 0.04) compared with control and resulted in a trend toward a 5% increase in PR interval (from 174 ± 11.2 to 182 ± 11.4 ms, P = 0.07). Conclusions: Intratracheal delivery of metoprolol effectively reduces ventricular rate during AF and accelerates conversion to normal sinus rhythm in a pig model of acetylcholine-induced AF.